Conversão do glicerol a propilenoglicol utilizando catalisadores a base de cobre - Rodrigues, Luan Guilherme Dias (2023)
The hydrogenolysis of glycerol is one of the main routes for the production of propylene glycol and will be the object of study of this work. In order to carry out a kinetic study aimed at increasing the glycerol conversion and the propylene glycol selectivity of the reaction, copper-based catalysts supported on zirconia, with different metal/support ratios, were used and they were synthesized by the coprecipitation method. The methods used for the characterization of the catalyst were thermogravimetric analysis, temperature programmed reduction and nitrogen physisorption. The reaction tests were carried out in a batch reactor and had their initial parameters defined from the literature, and they were the temperature of 200 ºC, pressure of 20 bar of hydrogen, reaction time of 4 hours, reaction volume of 20 mL, of which 20% of the mass was glycerol and the rest was water, and the catalyst mass of 350 mg. For the kinetic study, from the best performing catalyst, reactions were made by changing the values of one parameter at a time, and the alternative values of pressure were 5 and 10 bar, of temperature were 180 and 220 ºC, and the mass concentration of glycerol were 40, 60 and 80%. All the tests were performed, the catalyst with the best performance was the 60% ZrO2/Cu, with the values of 12.36% of conversion, 82.34% of selectivity to propylene glycol and a 10.18% yield of propylene glycol.